Case‐only designs for studying the association of antidepressants and hip or femur fracture. (March 2016) - de Groot, Mark C. H.; Candore, Gianmario; Uddin, Md. Jamal; Souverein, Patrick C.; Ali, M. Sanni; Belitser, Svetlana V.; Huerta, Consuelo; Groenwold, Rolf H. H.; Alvarez, Yolanda; Slattery, Jim; Korevaar, Joke; Hoes, Arno W.; et al.
Abstract: Purpose: The purpose of this study is to evaluate the performance and validity of the case‐crossover (CCO) and self‐controlled case‐series (SCCS) designs when studying the association between hip/femur fracture (HF) and antidepressant (AD) use in general practitioner databases. In addition, comparability with cohort and case–control designs is discussed. Methods: Adult patients with HF and who received an AD prescription during 2001–2009 were identified from UK's The Health Improvement Network (THIN) and the Dutch Mondriaan databases. AD exposure was classified into current, recent and past/non‐use (reference). In the CCO, for each patient, a case moment (date of HF) and four prior control moments at −91, −182, −273 and −365 days were defined. In SCCS, incidence of HF was compared between exposure states. Conditional logistic regression was used in the CCO and Poisson regression in the SCCS to compute odds ratios and incidence rate ratios, respectively. In CCO, we adjusted for time‐varying co‐medication and in SCCS for age. Results: Adjusted estimates for the effect of current AD exposure on HF were higher in the CCO (co‐medication‐adjusted odds ratio, THIN: 2.24, 95% confidence interval [CI]: 2.04–2.47; Mondriaan: 2.57, 95%CI [1.50, 4.43]) than in the SCCS (age‐adjusted incidence rate ratio, THIN: 1.41, 95%CI [1.32, 1.49]; Mondriaan: 2.14, 95%CI [1.51, 3.03]). The latter were comparable with the traditional designs. Conclusion: Case‐only designs confirmed the association between AD and HF. The CCO design violated assumptions in this study with regard to exchangeability and length of exposure, and transient effects on outcome. The SCCS seems to be an appropriate design for assessing AD–HF association. Copyright © 2016 John Wiley & Sons, Ltd.